2004
DOI: 10.1111/j.1523-1755.2004.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Uremic malnutrition is a predictor of death independent of inflammatory status

Abstract: The nutritional status of CHD patients predicts mortality independent of concomitant presence or absence of inflammatory response. Prevention of, and timely intervention to treat uremic malnutrition by suitable means are necessary independent of the presence and/or therapy of inflammation in terms of improving clinical outcomes in CHD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 31 publications
3
113
1
4
Order By: Relevance
“…serum phosphate levels), not hard outcomes (20 -24). Considering that phosphate-rich foods tend to be good sources of dietary protein (25,26) concern exists that long-term phosphate restriction may exacerbate protein energy malnutrition (27)(28)(29)(30), which is both common and potently associated with mortality among hemodialysis patients (31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…serum phosphate levels), not hard outcomes (20 -24). Considering that phosphate-rich foods tend to be good sources of dietary protein (25,26) concern exists that long-term phosphate restriction may exacerbate protein energy malnutrition (27)(28)(29)(30), which is both common and potently associated with mortality among hemodialysis patients (31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…This initially enhances the patients' appetite and improves their nutritional status. However, when patients continue to undergo haemodialysis over a longer period of time, there is an increased risk of malnutrition because of the loss of appetite stemming from uraemia and the haemodialysis technique (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…However, Pupim's group concluded that "the nutrition status of CHD patients predicts mortality independent of concomitant presence or absence of inflammatory response." 7 Dwyer et al found that increases in albumin at any level were associated with reduced short-term relative risk of mortality in CHD patients, even after adjusting for case mix, treatment assignments, protein catabolic rate, total cholesterol, and serum creatinine. 8 The combination of inflammation and protein malnutrition leads to decreased physical function, nutrient malabsorption, anorexia, weight loss, and impaired immune function.…”
Section: Methodsmentioning
confidence: 99%